Description of the epidemiology of healthcare-associated infections in the military hospital of Tunis - Ghaith, Aloui; Ali, Yousfi Mohamed; Sana, Bennour (International Journal of Infection Control, 2024)
Background: Healthcare-associated infections (HAIs) are the most common adverse events in healthcare delivery and the most frequently reported worldwide. Understanding its epidemiology can help stratify the problems and effectively determine prevention and control strategies. Objective: The aim of this study is to describe the epidemiology of HAIs in the military hospital of Tunis. Design: This is a retrospective descriptive study covering the year 2021. It concerns patients who stayed more than 48 h and who developed an infection meeting the criteria of HAIs. Results: A total of 380 HAIs were detected. This represents 2.49 per 1,000 days of hospitalization and 8% of admissions. Men were more affected than women. The anesthesia-intensive care department was the most involved (32.25%). Diabetes mellitus was the most encountered comorbidity (27%). The pulmonary system was the most affected site (46.8%). Germs were identified in 26% of cases. Klebsiella pneumoniae was the most incriminated germ (31%), followed by Staphylococcus aureus (26%). Vancomycin was the most prescribed broad-spectrum antibiotic (24%). Conclusions: Epidemiological surveillance is an essential tool to evaluate the impact of infection prevention and control policies. It would be desirable to reinforce the global policy in our hospital, which is mainly based on the respect of hygiene rules by the staff.